Desire and Empathy in Twentieth-Century Dystopian Fiction - Horan, Thomas (Palgrave Studies in Utopianism, 2018)
This book assesses key works of twentieth-century dystopian fiction, including Aldous Huxley's Brave New World, George Orwell's Nineteen Eighty-Four, and Margaret Atwood's The Handmaid's Tale, to demonstrate that the major authors of this genre locate empathy and morality in eroticism. Taken together, these books delineate a subset of politically conscious speculative literature, which can be understood collectively as projected political fiction. While Thomas Horan addresses problematic aspects of this subgenre, particularly sexist and racist stereotypes, he also highlights how some of these texts locate social responsibility in queer and other non-heteronormative sexual relationships, anticipating the ideas of various cultural theorists. In these novels, even when the illicit relationship itself is truncated, sexual desire fosters hope and community.